Victimology Aspects from the Perspective of Legal Protection of Children As Victims of Criminal Acts of Intercourse - Ayorbaba, Gracetin Yosepina; Hammar, Roberth K.R.; Silubun, Siria (LEGAL BRIEF, 2025)
This article examines the application of victimology in the legal protection of children as victims of sexual intercourse crimes in Indonesia. Using a normative juridical method complemented by conceptual and case approaches, it analyses child protection laws, the Juvenile Criminal Justice System Law, the Criminal Code, and selected court decisions, particularly from Papua and Maluku. The study explores how victims are positioned within the criminal justice process, whether as mere objects of evidence or as rights-bearing subjects entitled to protection, recovery, and restitution. The findings show that, although the legal framework formally recognizes preventive and repressive protection, implementation remains fragmented: trauma-informed procedures, child-friendly examinations, psychological support, and restitution orders are often absent or inconsistent. As a result, child victims frequently experience revictimization and unresolved psychological and social harm. Drawing on modern victimology and restorative justice theory, the article argues for a victim-centred juvenile justice paradigm that integrates preventive safeguards, comprehensive rehabilitation, and effective coordination among law-enforcement, child-protection agencies, and support institutions. Strengthening these elements is essential to realizing a truly child-friendly justice system and fulfilling the state’s constitutional mandate to protect children from sexual violence